Epigenetic Modulators as Treatment Alternative to Diverse Types of Cancer - Gutiérrez, Jorseth R.; Salgado, Arturo René Mendoza; Arias, Marcio De Ávila; San-Juan-Vergara, Homero; Rada, Wendy Rosales; Gómez, Carlos Mario Meléndez (Current Medicinal Chemistry, 2022)
DNA is packaged in an octamer of histones, forming chromatin, a complex of DNA and proteins. The structural matrix of a chromosome, chromatin and its changes are now regarded as important factors in controlling gene expression, which has sparked a lot of interest in understanding genetic pathways governing various diseases, including cancer. DNA methylation in the CpG dinucleotide as a transcriptional silencing mechanism, post-translational histone modifications such as acetylation, methylation, and others that affect chromatin structure, ATP-dependent chromatin remodelling, and miRNA-mediated gene silencing are all found to be important in various types of cancer. In this review, we analyze the main alterations in gene expression, epigenetic modification patterns in cancer cells, the main modulators and inhibitors of each epigenetic mechanism, and the molecular evolution of the most representative inhibitors, all of which point to a promising future for HAT, HDAC, non-glycoside DNMT inhibitors, and domain inhibitors.
Keywords: DNA